2021
DOI: 10.1093/jxb/erab354
|View full text |Cite
|
Sign up to set email alerts
|

miR825-5p targets the TIR-NBS-LRR geneMIST1and down-regulates basal immunity againstPseudomonas syringaein Arabidopsis

Abstract: Plants encode numerous intracellular receptors known as nucleotide-binding leucine-rich repeat receptors (NLRs) that recognize pathogen-derived effectors or their activity to activate defenses. MiRNA regulate NLR genes in many species, often triggering the production of phasiRNAs. Most such examples involve genes encoding NLR carrying coiled-coil domains, although a few include genes encoding NLRs carrying a Toll/interleukin-1 domain (TNL). Here, we characterize the role of miR825-5p in Arabidop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 79 publications
(173 reference statements)
2
13
0
Order By: Relevance
“…As BCTV V2, BCTIV V2 expression in a PVX heterologous system caused the induction of necrotic lesions in wt N. benthamiana , such as the ones produced during the HR, both at local and systemic levels in the wt N. benthamiana plants inoculated ( Figure 4 A,B). These results suggest that, in this PVX infection context, both proteins are avirulence factors that are directly or indirectly recognized by a resistance gene to trigger a defense response based on HR, known as effector-triggered immunity (ETI) [ 51 ]. It is remarkable that ectopic expression of BCTIV V2 from a 35S promoter did not cause any necrotic lesion in the infiltrated area in wt N. benthamiana leaves (similar results are observed when expressing BCTV V2) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As BCTV V2, BCTIV V2 expression in a PVX heterologous system caused the induction of necrotic lesions in wt N. benthamiana , such as the ones produced during the HR, both at local and systemic levels in the wt N. benthamiana plants inoculated ( Figure 4 A,B). These results suggest that, in this PVX infection context, both proteins are avirulence factors that are directly or indirectly recognized by a resistance gene to trigger a defense response based on HR, known as effector-triggered immunity (ETI) [ 51 ]. It is remarkable that ectopic expression of BCTIV V2 from a 35S promoter did not cause any necrotic lesion in the infiltrated area in wt N. benthamiana leaves (similar results are observed when expressing BCTV V2) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…For high-molecular weight and small RNA Northern blots, total RNA was extracted using Trizol reagent (invitrogen) from the infiltrated leaves, and it was used for hybridizations as described ([ 50 ]). Probe labelling for U6 and GFP siRNA detection was performed, as described in ([ 51 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, activation of PTI can upregulate the expression of a number of TNLs; however, such upregulation is dependent on Ca 2+ influx but not on ROS [ 145 ]. Finally, the overexpression of some of these PTI-induced TNLs resulted in increased defense outputs in Arabidopsis and N. benthamiana , suggesting that PTI triggers immune responses through TNL signaling pathways [ 99 , 147 , 148 , 149 ]. For a time, it was known that the EDS1-PAD4 complex was involved in basal immunity response, but the molecular mechanism was unclear [ 105 , 150 , 151 ].…”
Section: Pti and Eti As One Integrated Pathwaymentioning
confidence: 99%
“…In addition to targeting genes, it has been demonstrated that some miRNA-mediated cleavages of transcripts can trigger the production of phasiRNA ( Gai et al., 2018 ; Bélanger et al., 2020 ; López-Márquez et al., 2021 ; Shi et al., 2022 ). PhasiRNAs, another major class of small RNAs in plants, are involved in the control of plant biological processes ( Guo et al., 2018 ).…”
Section: Mir482/2118 Mediates Phasirna Generationmentioning
confidence: 99%